The Effect of Using Wooden Pile and Cast Concrete Reinforcement on Soft Soil Settlement in Graha Lentera Holtekamp Housing, Jayapura, Papua - Frans Denny Korwa; Duha Awaludin Karnitullah; Mujiati Mujiati; Bahtiar Bahtiar; Bernathius Julison (International Journal Labs, 2025)
Low shear strength will result in low bearing capacity and large (Settlement), even excessive settlement, and the compressibility of the soil will affect the shrinkage of the soil due to the influence of the groundwater level that occurs and will affect the stability of the buildings on it. soil stability through soil improvement techniques and soil reinforcement techniques. Soil improvement techniques are soil stability measures by improving the original soil characteristics, until they meet the technical requirements required by construction, such as increasing the bearing capacity and shear strength of the soil, decreasing soil compressibility, increasing or decreasing soil permeability, and so on. In this study, it was applied to unreinforced soil with a bearing capacity of 950.00 kPa with a qijin of 380.00 kN and with a decrease of 1.861 mm or 4.0%. Soil with reinforcement has a better carrying capacity compared to soil without reinforcement, so that soil with reinforcement gets greater load behavior, from the experiment with reinforcement of wooden piles (CK 8 I) gets a maximum load of 25.10 kN with a decrease of 5.90 mm or 11.80%. The maximum load acting on the ultimate unreinforced (pu) soil on the original soil is 13.68 kN with a qijin carrying capacity of 380.00 kN. Soil with wood pile reinforcement maximum working load of 25.10 kN with a drop of 5.90 mm or 11.80 %. Soil with reinforced cast-concrete maximum working load of 23.50 kN with a drop of 4.50 mm or 9.00 %.